Environmental dimension of pandemic COVID-19: case studies of Indonesia. Issue 1 (January 2021) - Hadi, S P; Ibrahim, M H; Prabawani, B; Hamdani, R S
Abstract: Pandemic COVID-19 adversely affects all aspects of life. Industries and transportation reduce its activities, causing a decline in demand for logistics significantly. In Indonesia, 2.8 people predicted will be laid off, 2.9-5.2 million people lose a job, unemployment will increase to 7.5%, poverty increases to 27.5 million people (10.2%), economic growth minus 5.32%. On the other side, the air quality index decreased from 155 at the end of March to 69 in April. The indicator of air quality (PM 2.5) decreased from 63.4 ug/m 3 to be 20.8 ug/m 3 . However, there has been increased in the amount of medical waste and energy consumption. This research aims to identify the impacts of pandemic COVID-19 on the environment and the commitment of the government to deal with climate change-related to SDGs. The result of research shows that the new normal increases the number of people infected by COVID-19 significantly. The government's commitment to dealing with climate change is decreased due to the policy to refocus and reallocate the budget to deal with pandemic COVID-19. It is required to balance the health aspect and economic aspect for the nation's sustainability and people's lives.